Effectiveness and safety of dolutegravir two‐drug regimens in virologically suppressed people living with HIV: a systematic literature review and meta‐analysis of real‐world evidence. Issue 6 (2nd February 2021) - Punekar, Y S; Parks, D; Joshi, M; Kaur, S; Evitt, L; Chounta, V; Radford, M; Jha, D; Ferrante, S; Sharma, S; Van Wyk, J; de Ruiter, A
Abstract : Objectives: Dolutegravir (DTG) is widely recommended within three‐drug regimens. However, similar efficacy and tolerability have also been achieved with DTG within two‐drug regimens in clinical trials. This study evaluated the real‐world effectiveness and discontinuations in people living with HIV‐1 (PLHIV) switching to DTG with lamivudine (3TC) or rilpivirine (RPV). Methods: This was a one‐arm meta‐analysis utilizing data from a systematic literature review. Data from real‐world evidence studies of DTG + RPV and DTG + 3TC were extracted, pooled and analysed. The primary outcome was the proportion of patients with viral failure (VF; ≥ 50 copies/mL in two consecutive measurements and/or ≥ 1000 copies/mL in a single measurement) at week 48 (W48) and week 96 (W96). Other outcomes included virological suppression (VS; < 50 copies/mL) and discontinuations (W48 and W96). Estimates were calculated for VF, VS as per snapshot (VSS) and on treatment analysis (VSOT), and discontinuations. Results: Pooled mean estimates of VF for DTG + 3TC and DTG + RPV were 0.8% [95% confidence interval (CI): 0.4–1.3] and 0.6% (95% CI: 0.0–1.6), respectively, at W48. VSS rate at W48 was 85.0% (95% CI: 82.3–87.5) for DTG + 3TC regimen and 92.4% (95% CI: 85.0–97.7) in the DTG + RPV regimen. The DTG + 3TC and DTG + RPV regimens led to discontinuations in 13.6% (95% CI: 11.1–16.2) and 7.2% (95% CI: 2.1–14.4) of patients, respectively, at W48. Similar results were observed at W96. Conclusions: Treatment with DTG + 3TC or DTG + RPV in clinical practice provides a low rate of VF and a high rate of VS when initiated in virologically suppressed PLHIV with diverse backgrounds.